The Impact of Good Corporate Governance, Company Size nn Corporate Social Responsibility Disclosure: Case Study of Islamic Banking in Indonesia - Qoyum, Abdul; Mutmainah, Lu’liyatul; Setyono, Joko; Qizam, Ibnu (Ekonomi Syariah IAIN Kudus, 2017)
Corporate Social Responsibility (CSR) disclosure is very important for Islamic banking, especially in the long term. CSR disclosure is expected can improve the reputation of the company, thus the performance of the company can increase. CSR disclosure is very close with the implementation of Good Corporate Governance in the company. The objectives of this research is to analyze the influence of the elements of good corporate governance (GCG) and company size on corporate social responsibility (CSR) disclosure by using Islamic Social Reporting (ISR) index. There are 10 Islamic banks in Indonesia as the sample of the research, from 2011 to 2014, then there are 40 annual reports that are determined through purposive sampling.Method of this research uses content analysis to evaluate CSR disclosure by using ISR index, whereaspanel regressionis employed to know the influence the elements of GCG (commissioners’ board, independent commissioners, shariah supervision board, and directors’ board) and company size on the CSR disclosure. The regression analysis suggest that the proportion of independent board of commissioners has negative effect on the CSR disclosure in Islamic banking. This research finding shows that independent commissioner is not able in providing maximum supervision on the company, which is affected by the lack of quality, and the dual job of independent commissioners at another company. While, company size has positive impact on the CSR disclosure, due to the strict regulation and society perception. This research finding may serve as an important input for the regulator to regulate properly related to the number of independent commissioner, its qualification and Islamic Social Reporting as a tool in disclosing their CSR.Pengungkapan Corporate Social Responsibility (CSR) sangat penting bagi perbankan syariah, terutama dalam jangka panjang. Pengungkapan CSR diharapkan dapat meningkatkan reputasi perusahaan, sehingga kinerja perusahaan dapat meningkat. Pengungkapan CSR sangat dekat dengan penerapan Good Corporate Governance di perusahaan. Tujuan dari penelitian ini adalah untuk menganalisis pengaruh elemen tata kelola perusahaan (GCG) dan ukuran perusahaan terhadap pengungkapan Corporate Social Responsibility (CSR) dengan menggunakan indeks Islamic Social Reporting (ISR). Ada 10 bank syariah di Indonesia dari tahun 2011-2014 yang menjadi sampel penelitian, maka ada 40 laporan tahunan yang ditentukan melalui purposive sampling. Metode penelitian ini menggunakan content analysis untuk mengevaluasi pengungkapan CSR dengan menggunakan indeks ISR. Sedangkan regresi panel digunakan untuk mengetahui pengaruh unsur GCG (dewan komisaris, komisaris independen, dewan pengawas syariah, dan dewan direksi) dan ukuran perusahaan terhadap pengungkapan CSR. Analisis regresi menunjukkan bahwa proporsi dewan komisaris independen memiliki pengaruh negatif terhadap pengungkapan CSR di perbankan syariah. Temuan penelitian ini menunjukkan bahwa komisaris independen tidak mampu memberikan pengawasan yang maksimal terhadap perusahaan. Hal ini dipengaruhi oleh kurangnya kualitas yang dimiliki, dan rangkap jabatan yang dimiliki oleh komisaris independen di perusahaan lain. Sedangkan, ukuran perusahaan berdampak positif terhadap pengungkapan CSR, karena ketatnya regulasi dan persepsi masyarakat. Temuan penelitian ini dapat menjadi masukan penting bagi regulator untuk mengatur dengan benar terkait dengan jumlah komisaris independen, kualifikasi dan ISR sebagai alat dalam mengungkapkan CSR mereka.